Solve for x: -2(3x - 15) - 4 = 56.

x = __

3 answers

To solve the equation \(-2(3x - 15) - 4 = 56\), follow these steps:

  1. Distribute the -2:

\[ -2 \cdot 3x + -2 \cdot -15 - 4 = 56 \]

This simplifies to:

\[ -6x + 30 - 4 = 56 \]

  1. Combine the constants on the left side:

\[ -6x + 26 = 56 \]

  1. Subtract 26 from both sides to isolate the term with \(x\):

\[ -6x = 56 - 26 \]

This simplifies to:

\[ -6x = 30 \]

  1. Now, divide both sides by -6:

\[ x = \frac{30}{-6} \]

This gives:

\[ x = -5 \]

Thus, the solution is:

\[ \boxed{-5} \]

are you sure this is correct

Let's double-check the solution step by step:

We start with the equation:

\[ -2(3x - 15) - 4 = 56 \]

  1. Distribute the \(-2\):

\[ -2 \cdot 3x + -2 \cdot -15 - 4 = 56 \]

This simplifies to:

\[ -6x + 30 - 4 = 56 \]

  1. Combine the constants on the left side:

\[ -6x + 26 = 56 \]

  1. Subtract 26 from both sides:

\[ -6x = 56 - 26 \]

This simplifies to:

\[ -6x = 30 \]

  1. Finally, divide both sides by -6:

\[ x = \frac{30}{-6} \]

which simplifies to:

\[ x = -5 \]

The calculation is indeed correct. The solution is:

\[ \boxed{-5} \]

This confirms that \(x = -5\) is the correct answer.